Synergistic Deoxynucleoside and Gene Therapies for Thymidine Kinase 2 Deficiency. Issue 4 (13th August 2021) - Lopez‐Gomez, Carlos; Sanchez‐Quintero, Maria J.; Lee, Eung Jeon; Kleiner, Gulio; Tadesse, Saba; Xie, Jun; Akman, Hasan Orhan; Gao, Guangping; Hirano, Michio
Abstract : Objective: Autosomal recessive human thymidine kinase 2 ( TK2 ) mutations cause TK2 deficiency, which typically manifests as a progressive and fatal mitochondrial myopathy in infants and children. Treatment with pyrimidine deoxynucleosides deoxycytidine and thymidine ameliorates mitochondrial defects and extends the lifespan of Tk2 knock‐in mouse (Tk2 KI ) and compassionate use deoxynucleoside therapy in TK2 deficient patients have shown promising indications of efficacy. To augment therapy for Tk2 deficiency, we assessed gene therapy alone and in combination with deoxynucleoside therapy in Tk2 KI mice. Methods: We generated pAAVsc CB6 PI vectors containing human TK2 cDNA ( TK2 ). Adeno‐associated virus (AAV)‐ TK2 was administered to Tk2 KI, which were serially assessed for weight, motor functions, and survival as well as biochemical functions in tissues. AAV‐ TK2 treated mice were further treated with deoxynucleosides. Results: AAV9 delivery of human TK2 cDNA to Tk2 KI mice efficiently rescued Tk2 activity in all the tissues tested except the kidneys, delayed disease onset, and increased lifespan. Sequential treatment of Tk2 KI mice with AAV9 first followed by AAV2 at different ages allowed us to reduce the viral dose while further prolonging the lifespan. Furthermore, addition of deoxycytidine and deoxythymidine supplementation to AAV9 + AAV2 treated Tk2 KI mice dramatically improved mtDNA copy numbers in the liver and kidneys, animal growth, and lifespan. Interpretation: Our data indicate that AAV‐ TK2 gene therapy as well as combination deoxynucleoside and gene therapies is more effective in Tk2 KI mice than pharmacological alone. Thus, combination of gene therapy with substrate enhancement is a promising therapeutic approach for TK2 deficiency and potentially other metabolic disorders. ANN NEUROL 2021;90:640–652